If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2(7+6x)=
We move all terms to the left:
2(7+6x)-()=0
We add all the numbers together, and all the variables
2(6x+7)-()=0
We add all the numbers together, and all the variables
2(6x+7)=0
We multiply parentheses
12x+14=0
We move all terms containing x to the left, all other terms to the right
12x=-14
x=-14/12
x=-1+1/6
| v+79=354 | | 8=s−10 | | 1.25+0.75h=4.00 | | -37=3X+13-2-7x | | m-401=363 | | 14+k=34 | | 3(2y+10)=5y | | 3(y−7)=−57 | | k-210=719 | | 7x-73=-1x+159 | | q9=4 | | 10(a+7)=50 | | 285=119-u | | 3(8n-4)=180 | | -5x+34=2x+10+5x | | x/3+5=28 | | 72=6(a+2) | | 12x-20=-84 | | 0.10m+24.95=0.20+19.95 | | 9=-3(2n-7) | | Y=5x-125 | | 7^2x-3=93 | | s/10=4 | | 3.953+8.95b=47.65, | | Y=125x-5 | | v/10=3 | | c-19c=-18c | | 5(c+40)=400 | | Y=125x+5 | | d5=−3 | | 5+y+y=57 | | 3/4b−2≤2b+8;b=−4 |